PENGUKURAN EFISIENSI PERBANKAN: STUDI KASUS KELOMPOK BANK BUKU I DAN BUKU II - Santoso, Teguh (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2017)
This study aims to measure the technical efficiency of banks (BUKU I and BUKU II categories). The efficiency calculation in this study uses Non-Parametric method, Data Envelopment Analysis (DEA). This research uses an operational approach in performing input and ouput specifications. The inputs are interest expenses, labor expenses, and other expenses. The result of technical efficiency calculation shows that both banks in BUKU I and BUKU II have less efficient in technical efficiency value, either with the assumption of CRS or VRS. However, the value of technical efficiency indicates that BUKU II banks have greater technical efficiency value than the banks in BUKU I category.